We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
779
1
avatar

{ y+2x+3z=-9 } 2y+4x+5z=-7 } -5x-6y-z=-1 }

 

thank you

 Nov 29, 2015

Best Answer 

 #1
avatar
+10

Solve the following system:
{2 x+y+3 z = -9 |     (equation 1)
4 x+2 y+5 z = -7 |     (equation 2)
-5 x-6 y-z = -1 |     (equation 3)
Swap equation 1 with equation 3:
{-(5 x)-6 y-z = -1 |     (equation 1)
4 x+2 y+5 z = -7 |     (equation 2)
2 x+y+3 z = -9 |     (equation 3)
Add 4/5 × (equation 1) to equation 2:
{-(5 x)-6 y-z = -1 |     (equation 1)
0 x-(14 y)/5+(21 z)/5 = (-39)/5 |     (equation 2)
2 x+y+3 z = -9 |     (equation 3)
Multiply equation 1 by -1:
{5 x+6 y+z = 1 |     (equation 1)
0 x-(14 y)/5+(21 z)/5 = -39/5 |     (equation 2)
2 x+y+3 z = -9 |     (equation 3)
Multiply equation 2 by 5:
{5 x+6 y+z = 1 |     (equation 1)
0 x-14 y+21 z = -39 |     (equation 2)
2 x+y+3 z = -9 |     (equation 3)
Subtract 2/5 × (equation 1) from equation 3:
{5 x+6 y+z = 1 |     (equation 1)
0 x-14 y+21 z = -39 |     (equation 2)
0 x-(7 y)/5+(13 z)/5 = (-47)/5 |     (equation 3)
Multiply equation 3 by 5:
{5 x+6 y+z = 1 |     (equation 1)
0 x-14 y+21 z = -39 |     (equation 2)
0 x-7 y+13 z = -47 |     (equation 3)
Subtract 1/2 × (equation 2) from equation 3:
{5 x+6 y+z = 1 |     (equation 1)
0 x-14 y+21 z = -39 |     (equation 2)
0 x+0 y+(5 z)/2 = (-55)/2 |     (equation 3)
Multiply equation 3 by 2/5:
{5 x+6 y+z = 1 |     (equation 1)
0 x-14 y+21 z = -39 |     (equation 2)
0 x+0 y+z = -11 |     (equation 3)
Subtract 21 × (equation 3) from equation 2:
{5 x+6 y+z = 1 |     (equation 1)
0 x-14 y+0 z = 192 |     (equation 2)
0 x+0 y+z = -11 |     (equation 3)
Divide equation 2 by -14:
{5 x+6 y+z = 1 |     (equation 1)
0 x+y+0 z = (-96)/7 |     (equation 2)
0 x+0 y+z = -11 |     (equation 3)
Subtract 6 × (equation 2) from equation 1:
{5 x+0 y+z = 583/7 |     (equation 1)
0 x+y+0 z = -96/7 |     (equation 2)
0 x+0 y+z = -11 |     (equation 3)
Subtract equation 3 from equation 1:
{5 x+0 y+0 z = 660/7 |     (equation 1)
0 x+y+0 z = -96/7 |     (equation 2)
0 x+0 y+z = -11 |     (equation 3)
Divide equation 1 by 5:
{x+0 y+0 z = 132/7 |     (equation 1)
0 x+y+0 z = -96/7 |     (equation 2)
0 x+0 y+z = -11 |     (equation 3)
Collect results:
Answer: | {x = 132/7     y = -96/7       z = -11
 

 Nov 29, 2015
 #1
avatar
+10
Best Answer

Solve the following system:
{2 x+y+3 z = -9 |     (equation 1)
4 x+2 y+5 z = -7 |     (equation 2)
-5 x-6 y-z = -1 |     (equation 3)
Swap equation 1 with equation 3:
{-(5 x)-6 y-z = -1 |     (equation 1)
4 x+2 y+5 z = -7 |     (equation 2)
2 x+y+3 z = -9 |     (equation 3)
Add 4/5 × (equation 1) to equation 2:
{-(5 x)-6 y-z = -1 |     (equation 1)
0 x-(14 y)/5+(21 z)/5 = (-39)/5 |     (equation 2)
2 x+y+3 z = -9 |     (equation 3)
Multiply equation 1 by -1:
{5 x+6 y+z = 1 |     (equation 1)
0 x-(14 y)/5+(21 z)/5 = -39/5 |     (equation 2)
2 x+y+3 z = -9 |     (equation 3)
Multiply equation 2 by 5:
{5 x+6 y+z = 1 |     (equation 1)
0 x-14 y+21 z = -39 |     (equation 2)
2 x+y+3 z = -9 |     (equation 3)
Subtract 2/5 × (equation 1) from equation 3:
{5 x+6 y+z = 1 |     (equation 1)
0 x-14 y+21 z = -39 |     (equation 2)
0 x-(7 y)/5+(13 z)/5 = (-47)/5 |     (equation 3)
Multiply equation 3 by 5:
{5 x+6 y+z = 1 |     (equation 1)
0 x-14 y+21 z = -39 |     (equation 2)
0 x-7 y+13 z = -47 |     (equation 3)
Subtract 1/2 × (equation 2) from equation 3:
{5 x+6 y+z = 1 |     (equation 1)
0 x-14 y+21 z = -39 |     (equation 2)
0 x+0 y+(5 z)/2 = (-55)/2 |     (equation 3)
Multiply equation 3 by 2/5:
{5 x+6 y+z = 1 |     (equation 1)
0 x-14 y+21 z = -39 |     (equation 2)
0 x+0 y+z = -11 |     (equation 3)
Subtract 21 × (equation 3) from equation 2:
{5 x+6 y+z = 1 |     (equation 1)
0 x-14 y+0 z = 192 |     (equation 2)
0 x+0 y+z = -11 |     (equation 3)
Divide equation 2 by -14:
{5 x+6 y+z = 1 |     (equation 1)
0 x+y+0 z = (-96)/7 |     (equation 2)
0 x+0 y+z = -11 |     (equation 3)
Subtract 6 × (equation 2) from equation 1:
{5 x+0 y+z = 583/7 |     (equation 1)
0 x+y+0 z = -96/7 |     (equation 2)
0 x+0 y+z = -11 |     (equation 3)
Subtract equation 3 from equation 1:
{5 x+0 y+0 z = 660/7 |     (equation 1)
0 x+y+0 z = -96/7 |     (equation 2)
0 x+0 y+z = -11 |     (equation 3)
Divide equation 1 by 5:
{x+0 y+0 z = 132/7 |     (equation 1)
0 x+y+0 z = -96/7 |     (equation 2)
0 x+0 y+z = -11 |     (equation 3)
Collect results:
Answer: | {x = 132/7     y = -96/7       z = -11
 

Guest Nov 29, 2015

22 Online Users

avatar